Record of paleo water divide locations reveals intermittent divide migration and links to paleoclimate proxies - Elhanan Harel; Liran Goren; Onn Crouvi; Naomi Porat; Tianyue Qu; Hanan Ginat; Eitan Shelef (Proceedings of the National Academy of Sciences, 2025)
Drainage divide migration alters the geometry of drainage basins, influencing the distribution of water, erosion, sediments, and ecosystems across Earth’s surface. The rate of divide migration is governed by differences in erosion rates across the divide and is thus sensitive to spatiotemporal variations in tectonics and climate. However, established approaches for quantifying divide migration rates offer only indirect evidence for the motion of the divide and provide only migration rate averages. Consequently, transience in divide migration cannot be resolved, hindering the ability to explore environmental changes that drive the dynamics of such potential transience. Here, we study a set of datable terraces identified as markers of paleo-divide locations, which provide direct evidence for the paleo motion of the divide. The location and age of the terraces reveal intermittent divide migration at timescales of 10 4 to 10 5 y, with phases of rapid migration—at rates more than twice the average—which coincide with documented regional paleoclimate fluctuations. These findings highlight the intermittent nature of divide migration dynamics over geomorphic timescales and its potential sensitivity to climate changes, underscoring the impact of such changes on the planform evolution of drainage basins.